2011
DOI: 10.1021/jo200882k
|View full text |Cite
|
Sign up to set email alerts
|

Probing Autoinducer-2 Based Quorum Sensing: The Biological Consequences of Molecules Unable To Traverse Equilibrium States

Abstract: Bacteria have developed a cell-to-cell communication system, termed quorum sensing (QS), which allows for the population-dependent coordination of their behavior via the exchange of chemical signals. Autoinducer-2 (AI-2), a class of QS signals derived from 4,5-dihydroxy-2,3-pentandione (DPD), has been revealed as a universal signaling molecule in a variety of bacterial species. In spite of the considerable interest, the study of putative AI-2 based QS systems remains a challenging topic in part due to the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
(94 reference statements)
0
26
0
Order By: Relevance
“…As with all α-diketone DPD analogues, the final acid-catalysed deprotection was carried out without purification or concentration of the resulting solution; it has previously been shown that the tert -butyldimethylsilanol by-product is non-toxic and inactive up to 100 µM against both V. harveyi and S. Typhimurium. 7 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with all α-diketone DPD analogues, the final acid-catalysed deprotection was carried out without purification or concentration of the resulting solution; it has previously been shown that the tert -butyldimethylsilanol by-product is non-toxic and inactive up to 100 µM against both V. harveyi and S. Typhimurium. 7 …”
Section: Resultsmentioning
confidence: 99%
“…2 We have previously investigated the use of carbocyclic analogues to mimic fixed ring-closed conformations of DPD (DHMP and triHMP, Figure 2). 7 However, the direct analogue DHMP had no significant effect against either V. harveyi or S. Typhimurium, and triHMP showed only limited antagonism in V. harveyi . DFT calculations suggested limited hydration at the C3 ketone of DHMP, a requirement for formation of the borate diester.…”
Section: Introductionmentioning
confidence: 99%
“…VBNC cultures were prepared as described above. The synthetic autoinducer (s)-4,5-dihydroxy-2,3-pentanedione (DPD) (OMM Scientific, Dallas, TX) spontaneously forms the quorum sensing molecule AI-2 in liquid suspension (31). AI-2 was prepared by adding a 10-fold molar excess of boric acid to DPD, making a 50 M DPD stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of these multiple C1-alkyl-DPD derivatives in V. harveyi depended on the assay conditions; they were found to function as either antagonists or synergistic agonists (LaSarre and Federle 2013; Defoirdt et al 2012;Lowery et al 2008). However, carbocyclic analogues of DPD did not display significant quenching activities in S. typhimurium or V. harveyi (Tsuchikama et al 2011;Guo et al 2013). Generally, AI-2 QS antagonists can exhibit two different types of activities being antagonists or synergistic agonists (LaSarre and Federle 2013).…”
Section: Targeting Ai-2 Receptorsmentioning
confidence: 99%